Credit market imperfections, financial market regulation and business cycles in Eastern Europe - Katja Drechsel; Frank Westermann (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Credit market imperfections give rise to boom-bust cycle episodes in emerging markets. In the present paper, we aim to provide a comprehensive analysis for Eastern Europe. We focus on documenting credit market imperfections, asymmetric financing opportunities across sectors, and business cycle fluctuations at the aggregate and sectoral level. The results will be discussed in the policy context of the re-regulation of the financial system. We will propose in an unconventional way to think about the early introduction of the Euro currency.
Keywords: F34; F36; G32; G38; 330; asymmetric financing opportunities; currency mismatch; sectoral business cycles